2004
DOI: 10.1063/1.1827917
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of Mn-doped ZnO multileg nanostructures and Mn-related Raman vibration

Abstract: Mn-doped ZnO multileg nanostructures were synthesized via in situ thermal oxidation of Zn and MnO2 powder. Spectroscopic measurements show that Mn ions have been doped into the lattice positions of Zn ions, which strongly induce growth of the observed ZnO multileg nanostructure. It is revealed that the growth mechanism of this kind of multileg ZnO:Mn nanostructure is different from the traditional vapor–solid or vapor–liquid–solid nucleation model of ZnO nanostructures. A possible mechanism is discussed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
93
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 25 publications
14
93
2
Order By: Relevance
“…Good agreement with experimental spectrum was obtained using the following spin Hamiltonian parameters: = 2 00232, A = 80 G, D = 225 G and E = 10 G. In simulation, Gaussian-shaped lines with an internal peak-to-peak linewidth ∆B = 8 G were used. The calculated values of the spin Hamiltonian parameters agree reasonably well with the values reported in the literature for Mn 2+ doped ZnO single crystal [20]. It was also observed that the obtained values of the spin Hamiltonian parameters did not change much with temperature in the 4-300 K range, indicating on a rather weak contact with the surrounding lattice.…”
Section: Resultssupporting
confidence: 79%
“…Good agreement with experimental spectrum was obtained using the following spin Hamiltonian parameters: = 2 00232, A = 80 G, D = 225 G and E = 10 G. In simulation, Gaussian-shaped lines with an internal peak-to-peak linewidth ∆B = 8 G were used. The calculated values of the spin Hamiltonian parameters agree reasonably well with the values reported in the literature for Mn 2+ doped ZnO single crystal [20]. It was also observed that the obtained values of the spin Hamiltonian parameters did not change much with temperature in the 4-300 K range, indicating on a rather weak contact with the surrounding lattice.…”
Section: Resultssupporting
confidence: 79%
“…In addition to the normal modes of ZnO [5], the spectra of the Mn-doped ZnO crystals present two well-defined peaks at 523.3 cm -1 and 531 cm -1 which are obviously related to the manganese impurity. One of these two modes has already been observed near 522 cm -1 and attributed to the presence of Mn dopants in ZnO [6]. In fact, many other modes found in ZnO crystals doped with various impurities have already been reported in the literature [6][7][8][9].…”
Section: Raman Scattering Measurementsmentioning
confidence: 88%
“…One of these two modes has already been observed near 522 cm -1 and attributed to the presence of Mn dopants in ZnO [6]. In fact, many other modes found in ZnO crystals doped with various impurities have already been reported in the literature [6][7][8][9]. Some of these modes have since been identified to be normally silent B1 modes of wurtzite ZnO, activated by the breakdown of the translation crystal symmetry [10].…”
Section: Raman Scattering Measurementsmentioning
confidence: 90%
“…Moreover, layers codoped with two impurities (ZnO:Al:Mn) show essentially the same behavior, as far as the 530 cm -1 mode is concerned, and its relative importance increases with the Mn dose as can be seen in Fig 4c. Thus, we conclude that the extra mode is undoubtedly associated with Mn ions or atoms. As a matter of fact, such an extra mode has been observed before in ZnO:Mn doped films [4,13] and has been interpreted as a local mode due to Mn substituting Zn in a lattice site [14]. Although such an assignment seems reasonable, the effects of plasmon-phonon coupling, known to be important for GaAs:Mn [15], should be investigated by combining Raman and FIR spectroscopies.…”
Section: Contributedmentioning
confidence: 93%